2019
DOI: 10.3390/ijerph16234682
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with the Aesthetic Effect and Quality of Life for Women after Breast Conserving Therapy (BCT)—Preliminary Research

Abstract: All methods of breast cancer treatment may potentially lead to breast deformities, which are often associated with the reduced mental well-being of patients. Breast conserving therapy (BCT) is commonly used, and its core element is breast conserving surgery (BCS).The aim of this study was to determine the level of satisfaction with the aesthetic outcome of surgery and quality of life (QoL) of breast cancer patients undergoing BCT in a longitudinal study performed three months, six months and 12 months after su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
3
8
4
Order By: Relevance
“…In our study, the mean ''satisfaction with breasts'' scores were slightly higher than those of Krzos et al 32 The reported mean scores were 56.0 before surgery, 63.0 at 3 months after surgery, and 62.2 at the 1-year follow-up evaluation. 30 In another study by O'Connell et al 30 evaluating 200 patients 1 to 6 years after BCT, the mean ''satisfaction with breasts'' score was 69.9, comparable with our results at the 1-year follow-up evaluation.…”
Section: Discussioncontrasting
confidence: 85%
“…In our study, the mean ''satisfaction with breasts'' scores were slightly higher than those of Krzos et al 32 The reported mean scores were 56.0 before surgery, 63.0 at 3 months after surgery, and 62.2 at the 1-year follow-up evaluation. 30 In another study by O'Connell et al 30 evaluating 200 patients 1 to 6 years after BCT, the mean ''satisfaction with breasts'' score was 69.9, comparable with our results at the 1-year follow-up evaluation.…”
Section: Discussioncontrasting
confidence: 85%
“…For Breast-Q the average patient was satisfied with the outcome, with scores higher than reported by studies that assessed QOL of patients undergoing breast conserving surgery [ 36 , 37 ], and all domains scored well in internal and external validity. Regarding average sexual well-being, this was reported to be stably low in our study, likely associated with PND itself.…”
Section: Discussionmentioning
confidence: 73%
“…In Brazil 15 it was reported that there was significant difference in the physical functioning and social interaction scoring with better QoL reported in conservation surgery group, especially in younger population and educated participants. Krzos et al 16 reported from Poland that better aesthetic outcomes resulted in improved QoL in terms of psychosocial parameters in all stages of observation.…”
Section: Discussionmentioning
confidence: 99%